К вопросу о влиянии поперечно-угловых колебаний корпуса легкобронированных колесных машин на точность стрельбы - Мельник, Б. А. (НТУ "ХПИ", 2012)
В работе предложена методика оценки влияния поперечно-угловых колебаний корпуса ЛБКМ на точность выстрела и доказана необходимость учета этих колебаний при проведении структурно-параметрического синтеза систем стабилизации вооружения ЛБКМ.

The method of estimation is in process offered influence of transversal-angular swinging of body of the armored wheeled machines on exactness of firing. The necessity of account of these swinging during the holding of structural-parametric synthesis of the armament stabilizing systems is proven.
To the question about influence of transversal-angular swinging of body of the armored wheeled machines on exactness of firing
Keywords: техника бронетанковая; модуль боевой; бронетранспортер; вооружение; стабилизатор; пушка